Teknisk och ekonomisk analys av en bränslekonvertering vid SIA TallOils pelletsfabrik - Johnsson, Gustaf (SLU/Dept. of Bioenergy, 2007)
At SIA TallOil's pellets factory in Latvia wood shavings and saw dust are dried with flue gases from a gas burner. TallOil wants to replace the gas with a biofuel that is available at the pellet plant. The reason for this is the unstable gas market in Europe in combination with the fact that TallOil wants to improve its profile as supplier of renewable bio fuels. In this project the technical and economical possibilities for a fuel conversion to ether bark powder, wood shavings or wood powder have been investigated. These fuels should be burned in one of the following applications: TPS BioSwirl, VTS Multifuel burner or Saxlunds bio fuel combustion plant